Oddźwięk wyboru Polaka na papieża w 1978 roku w świetle materiałów SB i PZPR na ziemi lubuskiej = The choise of a Polish Pope in 1978 as reflected in the records by the secret police and the Polish United Workers' Party in the province of Ziemia Lubuska - Bartkowiak, Przemysław (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
On Ocrober 16, 1978, from Vatican came the news that Cardinal Karol Wojtyła - a Pole, archbishopof Cracow - had been elected pope. The news spread rapidly across the country and filied the hearts of most Poles with joy and national pride in having a countryman on the throne of the Holy See.
Keywords: Ziemia Lubuska; Jan Paweł II, papież (1929-2005); materiały archiwalne